Translation of the Quran in Tolaki: a Perspective of Religious Moderation, and Islamic Law - Gunawan, Fahmi; Khairunnisa, Ainy (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This study focuses on the study of the translation of the Qur'an in Tolaki culture in Southeast Sulawesi from the perspective of religious moderation and its influence on Islamic law, as well as the factors that influence the translation. The method used is the descriptive analysis of the verses of religious moderation in Tolaki culture and Islamic law. The results of the study indicate that the verses of religious moderation include national commitment, tolerance, peace, and adaptive culture. In translating the verses of religious moderation, the translators used translation techniques such as established equivalence, transposition, modulation, reduction, discursive creation, literalism, borrowing, compensation, explicitness, addition, and adaptation. Socio-culturally, the Tolaki people have several concepts of religious moderation that can prevent potential unrest and conflict, such as the concept of medulu (self-esteem; togetherness), mepokoaso (unity), meohai (loyalty to the leader), mbeohai (brotherhood), mbeohai (loyalty to the leader); mbeohai (brotherhood), mombokulaloi (respect), samaturu (mutual cooperation), mombehunggaia (openness), mbendeporombu (deliberation and consensus), meloo mbenao (humility), mondotu'a (peace), and mombalalo (tolerance). The implications for the Tolaki community in Southeast Sulawesi are seen in the relatively high attitude towards religious moderation. The values of local wisdom that are embraced facilitate expanding opportunities for sustainable harmony and peace while minimizing the prevalence of conflict in society.